Perancangan Sistem Informasi Pemesanan Jasa Travel Pada Travel Jaya Kota Bengkulu Berbasis Web - Riski Riski; Yetman Erwadi (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The rapid acceleration of information technology currently demands the transportation service industry to modernize its operational management into an integrated digital ecosystem. Travel Jaya Bengkulu City, as a passenger transport provider, still faces efficiency challenges due to conventional procedures in reservation, manifest recording, and fleet coordination. This research is positioned to formulate a comprehensive blueprint of the Travel Jaya Bengkulu City Transportation Booking Information System that is both collaborative and systematic. System engineering adopts the Waterfall method as a structured development framework, ranging from the requirement analysis phase to data architecture modeling. The process design and data relationships are thoroughly resolved using Data Flow Diagrams (DFD), Entity Relationship Diagrams (ERD), and MySQL database structures. The output of this research delivers an information system design based on a Single Gateway Login that synchronizes the functional boundaries of three primary users: Admin as the central controller, Customers as independent consumers, and Drivers as field executors. Through this interaction model, consumers can reserve tickets and dynamically choose seat positions, admins can validate financial statements and manage master data centrally, and drivers are equipped with a responsive passenger manifest information module. Conceptually, this resulting design is declared valid to serve as a fundamental cornerstone in automating Travel Jaya's internal administration, strengthening database validity, and presenting a more practical, secure, and transparent transaction model for the public.